Effect of hydrothermal and washing treatment of banana leaves on co-gasification reactivity with coal. (February 2019) - Mosqueda, Alexander; Medrano, Katleya; Gonzales, Hazel; Yoshikawa, Kunio
Abstract: Reactivity of the solid fuel is one of the important characteristic in gasification. In this study, the reactivity in CO2 -gasification of hydrochar and washed hydrochar derived from banana leaves by hydrothermal and washing treatment was examined using thermogravimetric analyzer. The alkali metals (K and Na) retained in the hydrochar after hydrothermal and washing treatment was analysed. The results showed that the gasification reactivity of hydrochar and washed hydrochar was lower than its biomass origin due to the reduction of alkali content. Blending of hydrochar and washed hydrochar with anthracite coal enhanced the co-gasification reactivity that was attributed to the synergistic effect caused by the catalytic effect of the retained alkali metals. Hydrothermal and washing treatment not only improved the fuel properties and reduced the ash content of banana leaves as well as influenced the co-gasification reactivity with coal.